Dinamika Kemunculan dan Persinggungan Paradigmatik Tasawuf al-Hârith al-Muhâsibî - Riyadi, Abdul Kadir (ISLAMICA: Jurnal Studi Keislaman, 2014)
This paper tries to expose critically and analitically the historical dimension of tasawuf as far as its epistemological development is concerned. It argues that as a system of knowledge, tasawuf constitutes part and parcel of the larger Islamic epistemological system and shares with other forms of knowledge in its historical dimension. By referring in particular to the evolution of sufistic ideas in its early period as represented by the thought of al-HÃ¢rith al-MuhÃ¢sibÃ®, the paper tries to show that tasawuf cannot be discussed in isolation from such knowledge as fiqh, kalam, and philosophy. All these are related to one another historically and may be understood as influencing each other in such a way that theyâat some levelâshare the same epistemological roots. The paper, however, is not very much concerned with this similarity, as much as it is interested in finding out the dynamic tension between tasawuf and other forms of knowledge; tension that inevitably contributed in the very development and progress of this spiritual dimension of Islam.